Patches - Miles, Ellen (London Scholastic Inc., 2008)
Poor Patches is tied up in a garage and all alone. His owners love him but don't know how to look after him - can Jack and Lizzie show them how?
Keywords: Puppies -- Dogs -- Dog adoption